Mapping Smart-Grid Modernization in Power Distribution Systems - Oguah, Samuel (World Bank, Washington, DC, 2015)
Smart grids are an essential element in improving efficiency that is relevant to utilities in all countries - from advanced utilities with robust grids to those whose grids barely keep up with demand. This note provides practical guidance for stakeholders in defining smart-grid goals, identifying priorities, and structuring investment plans. While most of these principles apply to any part of the electricity grid (transmission, distribution, off-grid), the note focuses on the distribution network. Modernizing the grid can help utilities address issues in service delivery such as reducing technical and commercial losses, promoting energy conservation, managing peak demand, improving reliability, integrating high levels of distributed generation (such as mini-grids and power sources with variable output), and accommodating the rising use of electric vehicles. To harness these benefits, it is essential that well-designed plans be developed for the implementation of smart-grid goals and objectives. Smart elements in a grid will differ greatly depending on the state of the power system and the country context. A smart-grid roadmap will therefore vary considerably across countries, but smart technology is essential for successful modernization of any grid.